2015
DOI: 10.1096/fj.15-281543
|View full text |Cite
|
Sign up to set email alerts
|

Retinol as a cofactor for PKCδ‐mediated impairment of insulin sensitivity in a mouse model of diet‐induced obesity

Abstract: We previously defined that the mitochondria-localized PKCδ signaling complex stimulates the conversion of pyruvate to acetyl-coenzyme A by the pyruvate dehydrogenase complex. We demonstrated in vitro and ex vivo that retinol supplementation enhances ATP synthesis in the presence of the PKCδ signalosome. Here, we tested in vivo if a persistent oversupply of retinol would further impair glucose metabolism in a mouse model of diet-induced insulin resistance. We crossed mice overexpressing human retinol-binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 113 publications
(182 reference statements)
0
10
0
Order By: Relevance
“…In mice with active protein kinase C, retinol supplementation showed that retinol is a metabolic cofactor involved in the regulation of mitochondrial fuel utilization ( 179 ).…”
mentioning
confidence: 99%
“…In mice with active protein kinase C, retinol supplementation showed that retinol is a metabolic cofactor involved in the regulation of mitochondrial fuel utilization ( 179 ).…”
mentioning
confidence: 99%
“…Its physiological functions include maintaining visual function [32], promoting immunoglobulin synthesis [33], and maintaining the stability of reproductive epithelial cells [34]. Recent research has focused on the physiological functions of vitamin A, and its metabolite atRA, such as regulating energy metabolism, insulin sensitivity, and lipid metabolism [35,36]. An epidemiological investigation reported that a low serum retinol concentration was a risk factor for obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the effect of RetSat on ROS is mediated by the saturation of the all- trans -retinol moiety associated with protein kinase Cδ (PCKδ). The π-conjugated system of all- trans -retinol mediates electron transfer from cytochrome c leading to the activation of PCKδ [33] signalosome with ensuing effects on glycolytic energy generation [34, 35]. It is, therefore, possible that RetSat may interfere with this pathway by breaking the π-conjugation system via the saturation of the C13-C14 double bond of all- trans -retinol.…”
Section: Discussionmentioning
confidence: 99%